Exploring late Paleoindian and early Archaic unfluted lanceolate point classification in the Southern Plains. (October 2015) - Jennings, Thomas A; Smallwood, Ashley M; Waters, Michael R
During the late Paleoindian and early Archaic periods, the Southern Plains witnessed a diversification in unfluted lanceolate point styles. The classification of these points into distinct and meaningful typological groups continues to play a fundamental role in building an understanding of cultural changes at the end of the last Ice Age. In this study, we analyze a sample of points from the Hogeye site, Texas to explore unfluted lanceolate point classifications. The results suggest the presence of at least three late Paleoindian/early Archaic point hafting traditions in the Southern Plains, an Angostura/Thrall Tradition, a Dalton/Golondrina Tradition, and a Plainview/St. Mary's Hall Tradition.